KORELASI POLA ASUH OTORITER TERHADAP HASIL BELAJAR PADA KELAS V SD 4 PIJI DAWE KUDUS - Fitri Handayani; Sekar Dwi Ardianti; M. Syaffruddin Kuryanto (Jurnal Prasasti Ilmu, 2021)
This study aims to determine the relationship between authoritarian in developing with elementary school student learning outcomes. This research is a quantitative correlation study conducted at SD 4 Piji Dawe District, Kudus Regency. The research subjects were 5th grade students of SD 4 Piji. Data collection techniques used include questionnaires, direct observation, interviews, research documentation. Interviews were conducted with students and the main. In analyzing the data, a Likert scale model is used, namely the assessment using a scale of 1 to 4. Respondents are expected to provide an opinion on each question item ranging from 'always' to 'never' by circling or cross-marking the answers to be selected by the respondent on the questionnaire sheet. The results showed that there was a significant correlation between authoritarian parenting and learning outcomes of SD 4 Piji Dawe Kudus with a score of r table (-0.792 bigger than 0.433) with a significance value of 0.000, which means less than 0.05 (0.000 smaller than 0, 05). From these data it can be concluded that there is a significant correlation between authoritarian parenting and learning outcomes at SD 4 Piji Dawe Kudus.